К определению параметров дробно-экспоненциальных ядер наследственности нелинейно-вязкоупругих материалов - Голуб, В.П.; Павлюк, Я.В.; Фернати, П.В. (Прикладная механика, 2013)
A problem is solved on determination of parameters of the fractional-
exponential hereditary kernels of nonlinearly viscoelastic materials. The methods of determination of parameters, which are using in the cubically nonlinear theory of viscoelasticity and in the nonlinear theories and which are based on conditions of similarity of the initial creep curves and the isochronous creep diagrams, are analyzed. The mentioned parameters are determined and experimentally approved for different materials: the oriented polypropylene, nylon fibers FM 3001 and 10001, microplastic, glass-reinforced plastics TC-8/3250, CBAM and the contact moulding one. Розв’язано задачу визначення параметрів дробово-експоненційних ядер спадковості нелінійно-в’язкопружних матеріалів. Проаналізовано методи визначення параметрів, що використовуються в кубічній теорії в’язкопружності та в нелінійних теоріях та ґрунтуються на умовах подібності первісних кривих повзучості та ізохронних діаграмах. Визначено та експериментально апробовано параметри дробово-експоненційних ядер спадковості для мікропластику, склопластику ТС-8/3250, склопластику СВАМ. Дано аналіз результатів (таблиці, графіки).